1999
DOI: 10.1021/cm991087u
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for the Growth of Silicalite Membranes on Stainless Steel Supports

Abstract: Silicalite membranes have been prepared using a novel seeding method. By sonicating silicalite seed crystals in the presence of a stainless steel mesh followed by a controlled hydrothermal synthesis step it has been shown by AFM, SEM, and simple diffusion measurements that coherent membranes are produced. The sonication step anchors the nanometer-sized zeolite seeds to the porous stainless steel support and the subsequent hydrothermal growth produces a zeolite membrane grown on this seed layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 26 publications
0
25
0
2
Order By: Relevance
“…It was interesting to note that the separation ℃ factor of membranes increased slightly after repeated calcination cycles, and this might be caused by the condensation of Si-OH on the crystal surfaces, which improved the hydrophobicity of silicalite-1 membranes. In order to avoid the formation of cracks during calcination, a lower calcination rate was applied by other researchers [15,16] . Work by Holmes et al [16] showed that the cracks would formed for membranes synthesized on stainless steel supports at a heating rate above 0.25 /min, so a lower calcin ℃ ation rate was performed.…”
Section: Thermal Stability Of Silicalite-1 Membranementioning
confidence: 99%
See 1 more Smart Citation
“…It was interesting to note that the separation ℃ factor of membranes increased slightly after repeated calcination cycles, and this might be caused by the condensation of Si-OH on the crystal surfaces, which improved the hydrophobicity of silicalite-1 membranes. In order to avoid the formation of cracks during calcination, a lower calcination rate was applied by other researchers [15,16] . Work by Holmes et al [16] showed that the cracks would formed for membranes synthesized on stainless steel supports at a heating rate above 0.25 /min, so a lower calcin ℃ ation rate was performed.…”
Section: Thermal Stability Of Silicalite-1 Membranementioning
confidence: 99%
“…In order to avoid the formation of cracks during calcination, a lower calcination rate was applied by other researchers [15,16] . Work by Holmes et al [16] showed that the cracks would formed for membranes synthesized on stainless steel supports at a heating rate above 0.25 /min, so a lower calcin ℃ ation rate was performed.…”
Section: Thermal Stability Of Silicalite-1 Membranementioning
confidence: 99%
“…In order to avoid the formation of cracks during calcination, the synthesized membranes were generally calcined at a low calcination rate because of different thermal expansion coefficients between supports and zeolite layers. For example, work by Holmes et al [15] showed that the cracks would be formed for membranes synthesized on stainless steel supports at a heating rate of above 0.25℃/min, so a lower calcination rate was performed. Increasing the calcination rate to 5 /min ℃ , both the flux and separation factor decreased, and the reason was not clear.…”
Section: Thermal Stability Of Silicalite-1 Membranementioning
confidence: 99%
“…Several reports have presented various preparation methods for zeolite nanoparticles coated onto diatomite. Anderson et al [35,36] proposed a process involving ultrasonically loading silicalite-1 seeds onto diatomite, followed by a hydrothermal growth process of the seeds. The obtained composite showed a low specific surface area (S BET , 29.2 m 2 /g) and micropore volume (V micropore , 0.01 cm 3 /g).…”
Section: Introductionmentioning
confidence: 99%